Devaluation and Output Growth: Evidence from Pakistan - Asif, Muhammad; Shah, Syed Qasim; Zaman, Khalid; Rashid, Kashif (Richtmann Publishing, 2011)
This article investigates the long run and short run effect of currency devaluation on output growth of Pakistan byapplying unit root and cointegration analysis. The data set includes annual observations for the period 1980-2009. Moreover, thisstudy examines four alternative but equally plausible hypotheses, each with different policy implications. These are: i) Real GDP causeReal Effective Exchange Rate (the conventional view), ii) Real Effective Exchange Rate cause Real GDP, iii) There is a bi-directionalcausality between the two variables and iv) Both variables are causality independent (although highly correlated). The empirical evidencefinds significant positive relationship between devaluation and output growth in long run, as well as in short run. Both in the long andshort run, output growth are affected by currency devaluations.